The relationship between creativity, artwork quality and intellectual maturity of third grade primary school students of diﬀerent socio-economic statuses - Aleksandrovic Stajić, Marija Z. (Sociološki pregled, 2018)
This paper presents an empirical research on the “relationship between creativity, artwork quality assessment and students’ intellectual maturity” (N = 150). Тhe research used the following instruments: the Goodenough–Harris Draw-a-Person test of intellectual maturity, a battery of tests for examining creativity, an insight into students’ artwork based on which the quality assessment was made and a specially formulated questionnaire for examining students’ socio-demographic characteristics. The statistical analysis has shown that there is a positive correlation between intellectual maturity and general creativity, as well as a positive correlation between intellectual maturity and artwork quality assessment. The results of the research did not confrm the existence of statistically signifcant diﬀerences in the level of creativity and the artwork quality assessment in relation to students’ socio-economic status.
Keywords: Students; Artwork; Creativity; Intellectual maturity